Foreign-owned firms and productivity-enhancing restructuring in Finnish manufacturing industries - Mika Maliranta (The Research Institute of the Finnish Economy (ETLA), 2005)
The direct contribution of foreign-owned companies (FOCs) to productivity-enhancing intra-industry restructuring in Finnish manufacturing is analyzed by means of a productivity decomposition method. It is found that the FOCs have had an increasing role on the micro-level productivity dynamics after the liberalization of the foreign-ownership legislation in 1993. However, when proportioned to the employment share, the change of their contribution seems less outstanding. Initially the restructuring component of the FOCs was disproportionally large but had normalized by the end of the 1990s. – – Tutkimuksessa selvitetään ulkomaalaissomisteisten yritysten suoraa vaikutusta tuottavuutta vahvistavaan, toimialojen sisällä tapahtuvaan toimipaikkarakenteiden muutokseen Suomen teollisuudessa. Kysymystä on tutkittu tuottavuuden hajontamenetelmää käyttäen. Havaitaan, että ulkomaalaisomisteisten yritysten merkitys tuottavuuden mikrotason dynamiikalle on lisääntynyt vuonna 1993 tapahtuneen ulkomaalaisomistuksen liberalisoinnin jälkeen. Toisaalta kun ulkomaalaissomisteisten yritysten kontribuutio suhteutetaan niiden työllisyysosuuteen, kontribuution muutoksen merkitys näyttää vähemmän esiinpistävältä. Alussa ulkomaalaisomisteisten yritysten merkitys oli suhteellisesti ottaen suuri, mutta tilanne tasaantui 1990-luvun jälkipuoliskolla.
Keywords: F23; O33; O47; 330; Foreign ownership; productivity decomposition; productivity-enhancing restructuring; Ulkomaalaisomistus; tuottavuuden dekomponointi; tuottavuutta vahvistava rakennemuutos; Verarbeitendes Gewerbe; Multinationales Unternehmen; Auslandsniederlassung; Reorganisation; Finnland